On the Front Lines: The Impact of Managerialism on the New York City Addiction Treatment Workforce. (November 2021) - Lewiskin, Jocelyn; Abramovitz, Mimi; Zelnick, Jennifer
Since the mid-1970s, neoliberal policies have relied on privatization and other tactics to down-size the state, transforming human service organizations in the process. The impact of this approach, also known as managerialism, has not been examined in addiction treatment, where the opioid epidemic has intensified the need for services. Using qualitative semi-structured interviews, we explore how managerialism has affected the workforce, service delivery, and the quality of care in New York City addiction treatment programs. Front-line and managerial staff identified threats to working conditions, including high caseloads and productivity demands; threats to service quality including standardization of practice, loss of professional discretion and serving only those most likely to succeed; and threats to worker well-being marked by stress, burn-out, and low morale. The contradictions between the goals of managerialism and addiction treatment threaten the ability to meet the needs of people struggling with addiction.